Structural and functional features of a class VI chitinase from cashew (Anacardium occidentale L.) with antifungal properties. (December 2020) - Oliveira, Simone T.; Azevedo, Mayara I.G.; Cunha, Rodrigo M.S.; Silva, Christiana F.B.; Muniz, Celli R.; Monteiro-Júnior, José E.; Carneiro, Rômulo F.; Nagano, Celso S.; Girão, Matheus S.; Freitas, Cleverson D.T.; Grangeiro, Thalles B.
Abstract: A partial cDNA sequence from Anacardium occidentale CCP 76 was obtained, encoding a GH19 chitinase (AoChi) belonging to class VI. AoChi exhibits distinct structural features in relation to previously characterized plant GH19 chitinases from classes I, II, IV and VII. For example, a conserved Glu residue at the catalytic center of typical GH19 chitinases, which acts as the proton donor during catalysis, is replaced by a Lys residue in AoChi. To verify if AoChi is a genuine chitinase or is a chitinase-like protein that has lost its ability to degrade chitin and inhibit the growth of fungal pathogens, the recombinant protein was expressed in Pichia pastoris, purified and biochemically characterized. Purified AoChi (45 kDa apparent molecular mass) was able to degrade colloidal chitin, with optimum activity at pH 6.0 and at temperatures from 30 °C to 50 °C. AoChi activity was completely lost when the protein was heated at 70 °C for 1 h or incubated at pH values of 2.0 or 10.0. Several cation ions (Al 3+, Cd 2+, Ca 2+, Pb 2+, Cu 2+, Fe 3+, Mn 2+, Rb +, Zn 2+ and Hg 2+ ), chelating (EDTA) and reducing agents (DTT, β-mercaptoethanol) and the denaturant SDS, drastically reduced AoChi enzymatic activity. AoChi chitinase activity fitted the classical Michaelis-Menten kinetics, although turnover number and catalytic efficiency were much lower in comparison to typical GH19 plant chitinases. Moreover, AoChi inhibited in vitro the mycelial growth of Lasiodiplodia theobromae, causing several alterations in hyphae morphology. Molecular docking of a chito-oligosaccharide in the substrate-binding cleft of AoChi revealed that the Lys residue (theoretical p K a  = 6.01) that replaces the catalytic Glu could act as the proton donor during catalysis. Graphical abstract: Image 1 Highlights: A class VI chitinase from Anacardium occidentale was produced in Pichia pastoris. The recombinant protein was purified and partially characterized. The purified chitinase inhibited mycelial growth of Lasiodiplodia theobromae. A mechanism for its chitinolytic and antifungal activity is suggested.